The Impact of a Lack of Government Strategies for Sustainable Water Management and Land Use Planning on the Hydrology of Water Bodies: Lessons Learned from the Disappearance of the Aculeo Lagoon in Central Chile - Alaniz-Baeza, A (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Several studies have focused on why the Aculeo Lagoon in central Chile disappeared, with a recent one concluding that a lack of precipitation was the main cause, bringing tremendous political consequences as it supported the argument that the government is not responsible for this environmental, economic, and social disaster. In this study, we evaluated in detail the socio-economic history of the watershed, the past climate and its effects on the lagoon’s water levels (including precipitation recycling effects), anthropogenic modifications to the lagoon’s water balance, the evolution of water rights and demands, and inaccurate estimates of sustainable groundwater extraction volumes from regional aquifers. This analysis has revealed novel and undisputable evidence that this natural body of water disappeared primarily because of anthropogenic factors (mostly river deviations and aquifer pumping) that, combined with the effects of less than a decade with below-normal precipitation, had a severe impact on this natural lagoon–aquifer system. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.